2021
DOI: 10.2174/1871530320666200825184924
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNAs in the Progression and Metastasis of Colon Cancer

Abstract: : MicroRNAs regulate gene expression at the posttranscriptional level by binding to the mRNA of their target genes. The dysfunction of miRNAs is strongly associated with the inflammation of the colon. Besides, some microRNAs are shown to suppress tumours while others promote tumour progression and metastasis. Inflammatory bowel diseases include Crohn’s disease and Ulcerative colitis which increase the risk factor for inflammation-associated colon cancer. MicroRNAs are shown to be involved in gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…For example, it was reported that the hypermethylation in homeobox gene body did not suppress the expression but rather activated their oncogene activity, leading to upregulated expression (42). Meanwhile, miRNAs and lncRNAs were also found to widely participate in regulating cancer-related gene expression (43,44). In the future, more in vivo and vitro studies are needed to illustrate the potential function of NTMT1 in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that the hypermethylation in homeobox gene body did not suppress the expression but rather activated their oncogene activity, leading to upregulated expression (42). Meanwhile, miRNAs and lncRNAs were also found to widely participate in regulating cancer-related gene expression (43,44). In the future, more in vivo and vitro studies are needed to illustrate the potential function of NTMT1 in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs function at the posttranscriptional level by regulating specific individual target mRNAs, or serve as general regulators of gene expression, simultaneously mediating hundreds of genes expression. Many studies have identified different miRNAs expression levels between neoplastic tissues and tumor-adjacent normal tissues in CRC ( 56 , 57 ). MiRNAs can act both as oncogenes or tumor suppressors, depending not only on their altered pathways but also on the primary location, such as colon or rectal cancer.…”
Section: Molecular Network Of Crcmentioning
confidence: 99%
“…Many evidence demonstrate that early screening of colorectal cancer can reduce their incidence and mortality. Thus, the identification of diagnosis or prognosis biomarkers can contribute to assessment of tumour initiation, progression and therapeutic response for colorectal cancer (Sampath et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yue et al (Yue et al, 2021) reported that NEDD4 could trigger colon cancer progression through microRNA-340-5p suppression. In summary, the identification of microRNAs in the blood, tissues, and faecal matter will help us use these microRNA as biomarkers in early detection of colon cancer and thus design strong targeted therapeutic strategies for inflammation-mediated colon cancer (Peng et al, 2018;Sampath et al, 2021).…”
Section: Introductionmentioning
confidence: 99%